Strategi Pemasaran Dalam Meningkatkan Kunjungan Wisatawan Di Objek Wisata Do Madatu Kabupaten Toraja Utara - Puspita Sari, Yensinta; Elisabet Pali; Abedneigo Carter Rambulangi (JURNAL ILMIAH EDUNOMIKA, 2025)
Yensinta Puspita Sari (2025), “Marketing Strategy to Increase Tourist Visits to Do Madatu Tourist Attraction, North Toraja Regency” This study aims to design a marketing strategy to increase tourist visits to Do Madatu tourist attraction, North Toraja Regency. The approach used is a Qualitative approach and SWOT analysis to determine the Strengths, Weaknesses, Opportunities and threats faced in marketing and tourism management. The results of the study indicate that the implementation of the 5A tourism marketing strategy is an important part of increasing tourist visits to Do Madatu tourist attraction, North Toraja Regency. The role of the local government in terms of tourism marketing can also be part of the supporting factors for the development of tourism itself. This strategy is expected to be able to increase tourist visits to Do Madatu Tourist Attraction, North Toraja Regency. Keywords: Marketing Strategy; SWOT Analysis; Tourism Marketing